On establishing generalized analytical phase control conditions in two body self-reacting point absorber wave energy converters. (1st February 2020) - Bubbar, K.; Buckham, B.
Abstract: It is widely suggested that step gains in wave energy converter power capture performance must be realized to achieve economic viability. One method of fulfilling power capture gains is to invoke resonant conditions between the device and the incoming ocean wave. However, a general method that can establish the prerequisites for achieving resonant conditions in an arbitrarily complex wave energy converter architecture is nonexistent. In this work, we present an analytical procedure, built on the mechanical circuit framework, for identifying the resonant conditions of an arbitrarily complex wave energy converter architecture. To demonstrate the procedure, we select three complex two body point absorber devices as a case study, each with a geometry controllable feature set. Through invoking resonant conditions in each architecture, we illustrate how the choice of topology has significant influence on the power capture characteristics of the WEC device. Selecting the highest performing architecture, we then reveal how the analytical equations can be applied to promote technology innovation by supplying design criterion prior to locking down the WEC design. Finally, we apply the analytics within a numerical case study and present a hierarchy describing the incremental performance improvements realized through implementing steps in control complexity for this device. Highlights: Proposed an analytical method to solve for the optimal phase control condition(s) in an arbitrarily complex WEC architecture. Proposed a generic analytical constraint equation for achieving resonant control via the optimal spar mechanical impedance. Demonstrated how the choice of WEC topology has a strong influence on the power capture potential of a self-reacting point absorber WEC. Numerically demonstrated how an inerter can be used to implement this constraint equation. Demonstrated via case study a hierarchy of WEC control objectives in relation to their step increases in power capture potential.